The experience of spirituality in coping and suicide prevention among patients with psychiatric disorders (Research, Society and Development, 2025)
Introduction: Evidence indicates that religiosity and spirituality (R&S) influence mental health and suicide risk, acting either as protection (hope, sense of purpose) or as risk factors (guilt, negative religious coping). There are still gaps regarding how psychiatric patients experience spirituality in coping with and preventing suicide. Objectives: To analyze how spirituality impacts coping and suicide prevention in patients with psychiatric disorders, exploring mechanisms, relationships with well-being, and gaps to guide future interventions. Methodology: Integrative review based on PRISMA and PICO adaptations. Databases: PubMed, BVS, and LILACS (2014–2024). Quantitative, qualitative, and theoretical studies were included; duplicates, out-of-scope, or incomplete texts were excluded. Results: A total of 86 records (11/18/2024–04/30/2025) were identified; after screening, 14 studies were included. Findings showed that spirituality, regular religious practice, life purpose, social support, and self-forgiveness were associated with lower suicidal ideation and behavior, while rigid beliefs, guilt, and perception of divine punishment increased vulnerability. Personal spirituality proved more relevant than institutional religiosity. Conclusion: R&S exert a multifaceted influence on suicide risk, acting as protection or risk depending on individual experience and context. Elements such as hope, purpose, and resilience reduce suffering and strengthen coping. Integrating the spiritual dimension into mental health care may promote a more holistic approach, although longitudinal studies are still needed to clarify mechanisms and support effective clinical strategies.